Oocyte and Embryo Cryopreservation in Porcine In Vitro Production Systems - Nguyen, Hiep Thi; Somfai, Tamas; Nguyen, Bui Xuan; Kikuchi, Kazuhiro; Uoc, Nguyen Thi; Linh, Nguyen Viet; Nhung, Nguyen Thi; Hong, Nguyen Thi; Hanh, Nguyen Van (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Cryopreservation of oocytes and embryos, in addition to sperm, are important for gene banking and flexible use of time and space. In pigs,  in vitro production (IVP) is not only important system for the utilization of sperm kept in gene banks, but also is one of basic technologies  for the production of genetically modified, disease models or xeno-transplantation materials for human. Porcine oocytes and embryos  are characterized by high lipid content that are very sensitive with cooling. Besides, in vitro embryos are weaker than those derived in vivo in term of cell number. Therefore, cryopreservation by vitrification is preferred to slow freezing. Especially, cryopreservation of porcine  oocytes is possible only by vitrification and germinal vesicle (GV) stage is better than MII stage in terms of cytoskeletal organization  and subsequent blastocyst formation. There are several different vitrification methods that have been applied on porcine IVP embryos  based on the difference in cryoprotectants or devices to date. In this review, we discuss about recent IVP system, cryopreservation of  oocytes and embryos in pigs.
Keywords: Cryopreservation,; Embryos,; In vitro,; Porcine oocytes,; Vitrification.